A micro-mechanical model for the homogenized limit analysis of out-of-plane loaded masonry walls - Milani, G. (2005)
The paper presents a novel micro-mechanical model for the homogenized limit analysis of out-of-plane loaded masonry walls. In the framework of homogenization combined with limit analysis, masonry thickness is subdivided in several layers and for each layer polynomial distributions for the stress fields are a-priori assumed inside a fixed number of sub-domains. In this way, a simple linear optimisation problem is derived in order to obtain out-of-plane homogenized failure surfaces of masonry. Then, the surfaces so recovered are implemented in FE limit analysis codes for upper and lower bound analyses on entire masonry panels out-of-plane loaded. Some of these numerical investigations are reported in the paper in order to show the reliability of the results obtained (in terms both of collapse loads and failure mechanisms) in comparison with experimental evidences.